The influence of large classes in the English language teaching-learning process in Ecuadorian high schools. - Sánchez Galarza, Patricio (2015)
This study aims to determine instructional, social, and psychological implications of large classes in the English teaching-learning process. The research sample consisted of five classes of English as foreign language (EFL), which belonged to a private high school located in Quito and had 35 students or more. The selected classrooms were from 8th basic year to 3rd of bachillerato. The research data was collected through a questionnaire. Participants were asked to decide their agreement or disagreement about 21 statements according to a Likert scale. The information was described by using relative frequencies; then, the results were contrasted with the literature and previous researches. The findings evidenced that large classes influenced the occurrence of an irregular feedback toward the learners, a less tense atmosphere in class, more chances to meet classmates, the fact of not remembering the pupils’ names by teachers, and a general relaxation of students during lessons.